2014
DOI: 10.1016/j.jhydrol.2013.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological behavior of a deep sub-vertical fault in crystalline basement and relationships with surrounding reservoirs

Abstract: International audienceCrystalline-rock aquifers generally yield limited groundwater resources. However, some highly productive aquifers may be encountered, typically near tectonic discontinuities. In this study, we used a multidisciplinary experimental field approach to investigate the hydrogeological behavior of a sub-vertical permeable fault zone identified by lineament mapping. We particularly focused our investigations on the hydrogeological interactions with neighboring reservoirs. The geometry of the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 70 publications
7
53
0
2
Order By: Relevance
“…2). Moreover, previous studies in the Armorican basement have identified a compartmentalization of these crystalline rock aquifers from hydrological, geochemical, geological and geophysical data (Ayraud et al, 2008;Roques et al, 2014), and from regional-scale numerical modeling (Goderniaux et al, 2013). Geochemical studies also showed specific chemical compositions of the water in the deep fractured aquifer, potentially including saline groundwaters Ayraud et al, 2008;Pauwels et al, 2013).…”
Section: Hydrogeological Settingmentioning
confidence: 94%
See 3 more Smart Citations
“…2). Moreover, previous studies in the Armorican basement have identified a compartmentalization of these crystalline rock aquifers from hydrological, geochemical, geological and geophysical data (Ayraud et al, 2008;Roques et al, 2014), and from regional-scale numerical modeling (Goderniaux et al, 2013). Geochemical studies also showed specific chemical compositions of the water in the deep fractured aquifer, potentially including saline groundwaters Ayraud et al, 2008;Pauwels et al, 2013).…”
Section: Hydrogeological Settingmentioning
confidence: 94%
“…Conversely, high groundwater productivities are associated with fault zones below the weathered zone. Indeed, groundwater resources at significant depth have been found in the Armorican bedrock (Le Borgne et al, 2006;Roques et al, 2014), and it can be considered that the fractured system constitutes a water reservoir in the conti- nental basement. Free groundwater circulation in crystalline environments has been reported from several studies (Banks et al, 1996;Larsson, 1987).…”
Section: Hydrogeological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Gleeson and Novakowski (2009) and de Vries and Simmers (2002) state that groundwater recharge and groundwater flow processes are generally controlled by climate, morphology and geological conditions. To this day, several researchers have looked at groundwater recharge and groundwater flow processes in various climatic regions and geological media, particularly those with a combination of permeable rock matrices and conductive fractures (Verbovsek and Kanduc, 2016;Roques et al, 2014;Monjerezi et al, 2011;Apaydin, 2010;Chilton and Foster, 1995). It was shown in these studies that basic assumptions regarding groundwater recharge and flow processes that are applicable to porous media are not necessarily relevant in fractured rock environments, especially at field scale.…”
Section: Introductionmentioning
confidence: 99%